Apropriações e usos dos conceitos de desinformação, fake news e pós-verdade na Ciência da Informação no Brasil - Santos, Maria Eduarda de Oliveira (2022)
The disinformation, fake news and post-truth are themes that have acquired notoriety and relevance in scientific research in the most varied areas of knowledge, among them, Information Science, an interdisciplinary field whose object is informational phenomena in all their complexity. That said, this study has the general objective of understanding how the appropriation and use of the concepts of disinformation, fake news and post-truth in the field of Information Science in Brazil is found. Regarding the methodological course, it is a documentary research, of a descriptive nature and a quanti-qualitative approach, which has as its empirical field the Postgraduate Programs in Information Science and as a corpus the dissertations and theses defended in the period of 2011 to 2021 in Brazilian PPGCIs. For data analysis/interpretation, basic statistics and the categorization technique will be used, present in the content analysis method, as systematized by Bardin (2011). After analyzing the 27 (twenty-seven) texts that were retrieved, it was possible to identify the recurrence of citation of some names such as: Pinheiro and Brito (2014), Demo (2000), Brito (2015) and Volkoff (2004) regarding disinformation; Leisure et. al. (2018) and Allcott and Gentzkow (2017) towards fake news, the concet of the Oxford Dictionary (2016) and D’Ancona (2018) prevailed on post-truth. Furthermore, from the categorization of the concepts of the themes studied, it was possible to perceive the conceptual plurality regarding the definitions of disinformation. The categories about fake news and post-truth were reduced, as the descriptions of both do not include so many considerations. It was found that Information Science, through postgraduate studies, has invested in research on the terms discussed, thus, it is evident that the area has been concerned with its social aspect, insofar as it discusses contemporary informational phenomena in the face of society.